Morphological and functional changes in kidneys caused by propranolol: effects of melatonin. - Kryvchanska, M. I.; Ryznychuk, M. O.; Pishak, V. P. (Морфологія / Morphologia / Morfologìâ, 2016)
Background. Beta-blockers, including propranolol, are widely used in clinical practice as effective heart medicines. By the spectrum of action, some of them are selectively blocking beta-blockers, which are located in the heart muscle, and called cardioselective (nebivolol, metoprolol, atenolol). Others (propranolol, oksyprenolol, pindolol), simultaneously affect β1- and β2-adrenergic receptors, referred to as non-selective. Objective. The aim of our study was to examine the value of blockade of beta-adrenergic receptors in the regulation of chronorhythms of excretory and ion-regulative renal functions. Determine the possible role of exogenous melatonin in mechanisms of correction of circadian renal function disorders and morphologic abnormalities of kidneys. Methods. Experiments conducted on 35 male rats. One group of rats was daily administered by intragastric propranolol at a dose of 2,5 mg/kg body weight at 19.00 for 7 days. Another group of rats received intraperitoneal exogenous melatonin (Sigma, USA) (0,5 mg/kg body weight) at standard daylight against previous administration of propranolol. Results. Our studies showed that exogenous melatonin is able to influence the basic parameters of renal function caused by propranolol. Obviously, these effects are realized by stimulating specific melatonin receptors located on the basolateral membrane of the initial divisions of proximal tubules, and to a lesser extent – in the glomeruli. Thus, administration of melatonin on the background of propranolol action increases the urine output, increases the speed of ultrafiltration in glomeruli at 42 %, reduces the effects of azotemia, increases the excretion of sodium, increases proximal and distal transport of this cation. Conclusion. The influence of melatonin in condition of propranolol action was characterized by pleiotropic effect.